Fibrin Glue Injections: A Minimally Invasive and Cost‐Effective Treatment for Post–Renal Transplant Lymphoceles and Lymph Fistulas. Issue 2 (13th October 2015) - Presser, N.; Kerr, H.; Gao, T.; Begala, M.; Paschal, S.; Shoskes, D. A.; Flechner, S. M.
Abstract : Pelvic lymphoceles/lymph fistulas are commonly observed after kidney allotransplantation, especially when the kidney is placed in a retroperitoneal position. While the majority are <5 cm in diameter and resolve without intervention, some may continue to enlarge, and cause local or systemic symptoms or graft dysfunction. Among 1662 recipients of both living and deceased donor kidney transplants between January 2003 and July 2014, we found 46 (2.7%) patients with symptomatic lymphoceles requiring intervention. We studied the clinical outcomes and charges for three treatment modalities including open surgical drainage (22), laparoscopic surgical drainage (11), and percutaneous fibrin glue injections into the drained lymphocele cavity (13). The patient demographics and clinical characteristics were comparable for each treatment group, although maintenance immunosuppressive drugs differed by era. We found fibrin glue injections resulted in significantly lower (p = 0.04) rates of recurrence (1; 7.7%) than either laparoscopic (6; 54%) or open surgical drainage (6; 27.3%). In addition, fibrin glue injections generated significantly (p < 0.001) lower median ($4559) charges compared to either laparoscopic ($26 330) or open surgical drainage ($23 758). Fibrin glue treatment has the advantage of being an outpatient procedure, performed with the patient under local anesthesia, and does not incur the expense of an operative procedure or hospital admission associated with laparoscopic or open surgery.